Дослідження згину полотна стрічкової пилки на шківах верстата - Ольховий, Іван; Дзюба, Лідія (КІНПАТРІ ЛТД, 2013)
The theoretical depending of changes of the distributed load, of the bending moment and of the transverse force for curved on the pulley saw blade plot were received during this research considering the shift deformation. The longitudinal deformation of this plot was examined by the method of tensometry
The research of the bending of band saw canvas to workbench’s pulley